Amdal Analysis on C Excavation Management in the Ngoro Area, Jombang Regency in the Perspective of the Feasibility Study of Islamic Business in Sharia Economics - Lailatul Berliana Ningsih; Abdur Rohman (Rihlah Iqtishad: Jurnal Bisnis dan Keuangan Islam, 2025)
This article aims to understand the management of C excavations on the environment in the Ngoro Jombang area and its implications according to Regional Regulation Number 8 of 2017 concerning environmental protection and management and biah fiqh. This research is included in qualitative research. To obtain data, researchers obtain it directly from the source without intermediaries from other parties, which is then processed. There are two data sources, namely primary and secondary data sources. Data collection by means of interviews, observation, documentation. After the data is collected, it is analyzed using descriptive methods. The results obtained from data analysis are that the management of excavation c is mining which includes: sand, gravel, the process of which is by dredging the soil until it has holes to make a profit. In this activity the impact is not only on local residents, but also on the earth and the surrounding nature. In law and Islamic jurisprudence, it is permissible on the condition that it is not allowed to be excessive and destroy the natural surroundings just to meet the needs and prosperity of the community